Transactional Communication Model Sellers Between and Buyers in Kendari City Market - Aboy, Abdul Sarlan Menungsa; Sari, Paramitha Purwita; Syahruddin, Syahruddin; Muslan, Muslan (Universitas Islam Balitar, 2023)
The problem that we want to observe is the transactional communication model between traders and buyers in the Kendari City market. The location of this research was carried out at the market in Kendari City. Transactional Communication Theory (Eric Berne in Mulyana 2002: 109) is the reference in this research. The number of informants was 20 people. Qualitative descriptive is a method for collecting data. The research results show that complementary transactions at the Kendari City Market occur because of the same attitude, mature attitudes between traders and buyers in interacting, cross transactions at the Kendari City Market occur because traders and buyers misinterpret the meaning of the message, transactions from both parties conveyed do not occur in agreement. Hidden transactions at the Kendari City Market occur because they assume that buying and selling matters are the main priority that must be done without paying attention to other conversations outside the buying and selling process.